Table of Content - - (Journal of Islamic Sciences, 2024)
Table of Content:1. Family Alienation And The Challenges Of The Technological AgeAmirah Mohammad Alajmi2. Controls and provisions of electronic financial papers (a comparative jurisprudential study)Mohammed Khalil Mohammed Alshaikhi3. The Abrogation Issue in Verses of Night Prayer: Applied StudyHanin Khalaf Al-Mawadiya4. The Islamic jurisprudence of the Prophet Mohammed in crisis managementNoureddine Abdelati Kailan
Keywords: Journal of Islamic Sciences